Freedom From The Traumatic Effect In Safe Haven Movie Script - Paruntu, Kezia Aviska; Wuntu, Ceisy N.; Mamentu, Agustine C. (Program Studi Pendidikan Bahasa Inggris, 2025)
This study explores the theme of freedom from traumatic effects as depicted in the film